(untitled) (Sustainability in Debate, 2023)
This research explores the potential of geographic intelligence in modelling optimal corridors for assessing alternative locations for power transmission lines at different stages of the study. The difficulties verified in the environmental licensing of new projects, the expansion of the national transmission system, and the lack of work to research techniques for formulating locational alternatives are motivating questions for this research. The investigation employs a multicriteria decision-making approach integrated with a geographic information framework to compute and map the feasibility corridors based on environmental constraints and stakeholder inputs. Findings reveal that the current decision-making process for implementing new power transmission lines involves disparate public and private entities operating non-integratively in a multi-level analysis and decision-making process. Through a case study utilising multicriteria analysis and expert consultations, the research demonstrates the applicability of spatial modelling in the locational planning of transmission projects. It highlights the model’s capacity to address the complexity inherent in such studies, aggregate analyses and decisions from various stakeholders, and enhance transparency in the decision-making process from energy planning to operational phases.